Azo dye decolorization in an up-flow bioelectrochemical reactor with domestic wastewater as a cost-effective yet highly efficient electron donor source. (15th November 2016) - Cui, Min-Hua; Cui, Dan; Gao, Lei; Wang, Ai-Jie; Cheng, Hao-Yi
Abstract: A major challenge of employing bioelectrochemical system (BES) for reductively degrading recalcitrant contaminants in industrial wastewater is lacking sufficient electron donors. In this work, domestic wastewater (DW) was demonstrated to efficiently drive BES for implementing the decolorization of azo dye, acid orange 7 (AO7). Side benefit was the simultaneous treatment of DW. Decolorization efficiency in BES fed with DW (RDW ) was found to be comparable with that either fed with glucose (RGlu ) or acetate (RAc ). Much lower reductant usage ratio was observed in RDW . As a result, when the ratio of electron donors to azo dye decreased to 4.4 mol COD mol −1 AO7, DE of RDW kept over 90% while DEs of RAc and RGlu were significantly dropped due to the insufficient electrons donation. Besides serving as electron donor, DW was proved to also provide some conductivity and buffer capacity. Accordingly, DE of RDW was less deteriorated when fully removing the external buffer slats. This study comprehensively revealed the feasibility and superiority of DW as a cost-effective electron donor source in BES and brings this technology closer to the practice. Highlights: DW was proved to be an efficient electron donor source in BES for decolorization. BES fed by DW showed comparable or even better DEs than that by acetate and glucose. DW as electron donor source gains benefits of cost-effective and concomitant treating. DW feeding BES could maintain high decolorization efficiency without external buffer.